FREEDOM OF ASSEMBLY: DEMOCRATIC SIGNIFICANCE, LEGAL REGULATION AND THE PROBLEM OF IMPLEMENTATION IN UKRAINE - Біденко, Ю.М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The freedom of assembly securing in international law and problem of its realization in Ukraine are considered. It is shown that in the absence of special law, public peaceful actions become a subject of regulation by local authorities and courts, what results frequent violations of this constitutional right. The analysis of the prospects and risks of bills pending before the Verkhovna Rada of Ukraine is also provided.